A method for locating and diagnosing cable abrasion based on broadband impedance spectroscopy. (August 2022) - Zhang, Haotian; Mu, Haibao; Lu, Xu; Tian, Jie; Zou, Xingyu; Zhang, Guanjun
Abstract: Modern power systems contain different types of cables and that makes it important to diagnose defects before they result in faults. Existing cable inspection methods, such as dielectric loss measurement and partial discharge, still fail to detect and locate weak cable defects. This paper presents a novel non-destructive method for detecting wear and aging defects based on broadband impedance spectroscopy (BIS) is proposed. A digital model of the cable distribution parameters is developed in this paper. The effects of different angular wear defects on the impedance spectroscopy were compared, and the degree of defects was successfully distinguished by discrete Fourier transform (DFT). The severity of the defect can be determined from the difference in peak height at the defect location after normalization. By using DFT and the Chebyshev Window it was also possible to identify two defects in the cable within 0.47% deviation of the defect position.